'Cinderella of the Education System': Margaret Thatcher's Plan for Nursery Expansion in 1970s Britain. (28th July 2017) - Danziger Halperin, Anna K
Abstract: The Department of Education and Science, led by then Secretary of State Margaret Thatcher, published a White Paper in December 1972 calling for a dramatic expansion of public nursery education, so that it might be available within a decade to all families with 3- and 4-year-old children who chose to utilize it. While this failed policy is seldom remembered today, and Thatcher's efforts to promote the care and education of young children are not considered part of her considerable legacy, the White Paper's policy propositions challenge understandings about the formation and consistency of both Britain's child care policy and 'Thatcherism'. During this period, Thatcher believed that extending the frontiers of the state was appropriate to promote child welfare during the crucial first years of life. She conceived of nursery education as serving a developmental and educational purpose for all children, quite separate from welfare provisions for poor families or work supports for women. It is this crucial, albeit arbitrary, distinction which explains how nursery education was envisaged as an exception to her advocacy of cutting welfare spending.